The rise of Sivagami : book I - Anand Neelakantan (Bahubali: before the beginning, 2017)
"Blessed by the sacred Gauriparvat, Mahishmathi is an empire of abundance. The powerful kingdom is flourishing under its king, who enjoys the support and loyalty of his subjects, down to his lowly slaves. But is everything really as it appears, or is the empire hiding its own dirty secret? Orphaned at a young age and wrenched away from her foster family, Sivagami is waiting for the day she can avenge the death of her beloved father, cruelly branded a traitor. Her enemy? None other than the king of Mahishmathi. With unflinching belief in her father's innocence, the fiery young orphan is driven to clear his name and destroy the empire of Mahishmathi against all odds. How far can she go in her audacious journey?"--Publisher's description.